Regional And International Linkages Of The Asean-5 Stock Markets: A Multivariate Garch Approach - Lee, Stan Shun Pinn; Kim, Leng Goh (Asian Academy of Management (AAM), 2016)
This paper examines the linkages among the ASEAN-5 stock exchanges, and their relationship with the Hong Kong and U.S. markets by using the multivariate GARCH approach for the period before and after the global financial crisis. The mean and volatility spillover effects are analysed. The mean, past-volatility, and past-shock spillovers between the ASEAN stock markets occurred to a lesser extent in the post-crisis period. While these findings suggest weaker linkages, the reaction to bad market news has strengthened after the crisis. The U.S. market is the main source to the mean spillover effects. Although the past-volatility and past-shock spillovers effects from the Hong Kong market are larger, the ASEAN markets tend to react more strongly towards unfavourable U.S. market news.